Metal clusters and cyclopolyenes: the face-capping coordination mode - Wadepohl, Hubert (Coordination chemistry reviews, 1999)
The synthesis, structure and chemistry of tri- and tetranuclear cluster complexes with face-capping C7H7 and C8H8 ligands are described. Synthesis of such complexes is based on mutual steric hindrance of two of the large cyclopolyenes, which cannot both occupy apical coordination sites in a M4 (M=Co, Rh) cluster. Reactions where the facial coordination of the cyclopolyene is retained include substitution of apical ligands and redox reactions with and without degradation of the metal cluster. A description of the characteristic features of the facial (μ3-) bonding mode of C7H7 and C8H8 is given, based on numerous crystal structures.
Gesehen am 29.01.2019